Analysis of the Potential and Implementation of Digital Sharia Financing for the Empowerment of Fisherwomen A Blue Economy Study in South Sulawesi - Indrawan Azis; Putri Purwandari Hasan; Laode Arahman Nasir (Faculty of Islamic Business and Management, 2025)
Women fishers play a strategic role in contributing to the coastal economy, engaging in activities ranging from production and processing to distribution and marketing of marine products. However, they continue to face significant barriers in accessing formal sources of financing due to limited collateral assets, low levels of financial literacy, and inadequate access to financial technology in coastal areas. The development of Islamic financial technology, or sharia fintech, presents an opportunity to provide a fair, inclusive, and Sharia-compliant financing system. This study aims to analyze the potential and implementation of a digital-based Sharia financing model for women fishers in South Sulawesi within the framework of a sustainable blue economy. The research adopts a qualitative approach with a case study conducted in Pangkajene and Islands Regency, South Sulawesi. Data were collected through semi-structured interviews with groups of women fishers and administrators of Islamic financial institutions, particularly Islamic cooperatives operating within coastal communities. Data analysis was conducted using thematic analysis, assisted by NVivo 12 Pro software. The results indicate that most women fishers are still in the early stages of the innovation diffusion process—specifically, the knowledge and persuasion stages—thus the utilization of Sharia fintech remains limited. Nevertheless, the potential for adopting Sharia fintech is promising if supported by continuous education, institutional mentoring, and the integration of empowerment programs based on the blue economy. This study recommends the development of an integrated digital Sharia financing model aligned with coastal women’s economic empowerment programs to strengthen financial inclusion in support of a sustainable blue economy.